Effect of nanomaterials inclusion on sustainability of cement-based concretes: A comprehensive review. (1st November 2021) - Onaizi, Ali M.; Huseien, Ghasan Fahim; Lim, Nor Hasanah Abdul Shukor; Amran, Mugahed; Samadi, Mostafa
Highlights: Nanomaterials can enhance the sustainability performance of concrete. Strength performance of concrete highly influenced by nanomaterials type and content. Environmental fitness of nanomaterials based concrete is discussed. Engineering properties and microstructure analysis of modified concrete are discussed. Abstract: Negative effects of carbon dioxide (CO2 ) emissions due to rapid development in several countries worldwide are of increasing concern for the sustainable growth. To overcome such problem, the production of less clinker-based modified concretes with lower levels of CO2 emission became challenging in the building sectors. Such concretes can offer satisfactory strength performance and durability in the construction sector. Meanwhile, various nanomaterials incorporated concretes generated immense interests for attaining the sustainability objectives in the civil engineering field. Based on these factors, a comprehensive sustainability assessment of diverse nanomaterials included cement-based concretes was made. In addition, the mechanisms behind the influence of different nanomaterials on the strength characteristics, workability and durability performances of the proposed improved concretes were examined. The past progress, recent drifts, ongoing challenges, effects on environmental sustainability, pros and cons of these nanomaterials-activated cement-based concretes were emphasized.